PENGARUH EXPERIENTIAL MARKETING SEBAGAI SUATU STRATEGI DALAM MENCIPTAKAN KEPUASAN DAN DAMPAKNYA TERHADAP LOYALITAS (Survei Pada Pelanggan Waroeng Spesial Sambal “Waroeng Ss” Cabang Sengkaling, Kota Malang) - Aprilia Hapsari; Achmad Fauzi (Fakultas Ilmu Administrasi Universitas Brawijaya, 2017)
This research aimed to examine and determine the effect of : Experiential Marketing consisting of variables Sense, Feel, Think, Act and Relate to Customer Satisfaction; the effect of Customer Satisfaction to Customer Loyalty; the effect of Experiential Marketing consisting of variables Sense, Feel, Think, Act and Relate to Customer Loyalty; Experiential Marketing on Customer Satisfaction and the impact to Customer Loyalty. The type of research was explanatory research with quantitative approach. The object of this research is Waroeng Special Sambal